PERBANDINGAN HASIL BELAJAR MAHASISWA SEBELUM DAN SESUDAH PROSES BELAJAR AKTIF MENGGUNAKAN KARTU ANATOMI GIGI (KABANOGI ) - Putri Rahmasari (FK IK UMY 2016, 2016)

(untitled)
Kartu Anatomi Gigi ( Kabanogi ) was one of the learning media which contained pictures and the explanations about the dentition morphology. It could be used to support the learning process of teeth anatomy to elaborate many skills, including the analytical thinking, social, empathy, interactive, and communicative skills. The reason why the researcher decided to use this media was due to the difficulties of dental students of 2014 class in PSPDG FKIK UMY to learn, understand, and memorize the teeth anatomy, especially for the specific characteristics of the dentition morphology. Therefore, the students needed a supplementary media to help them learning the teeth anatomy. Objective : To find out whether there was any difference in the students’ study results before and after the active learning process using Kabanogi. Method : The type of this research was a quantitative pre-experiment with the research design of one-group pre-post-test. The data analysis technique used the inferential statistic with Wilcoxon signed-rank test. Result : This research showed that there was a significance difference between the students’ study result before and after the active learning process using Kabanogi with the probability value of 0,000